The Role Of Company Size As A Moderating Variable Against Financial Statement Fraud: The Beneish Model Perspective - Sarwenda Biduri; Sigit Hermawan; Wiwit Hariyanto; Sriyono Sriyono; Cintya Devi Retno Ardianti (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to prove the influence of External Pressure, Ineffective Monitoring, Quality of External Auditors, Changes in Auditors and Frequency of CEO Depictions and Company Size as a moderation of Fraud in a company's Financial Statements. Methodology/approach: In this study, researchers used a type of quantitative research. Purposive sampling was used as a technique in determining the sample for this study. The data used are company annual reports and the population in this study are companies engaged in the textile and garment manufacturing sub-sector for the 2017-2021 period with a total sample of 55. Findings: This study states that the variables Quality of External Auditors and Frequency of CEO Descriptions have an effect on fraudulent acts in reports financial statements, while the variables of Ineffective Oversight, External Pressure and Change of Auditor have no effect on fraudulent acts in financial statements. For the moderating variable in this study, company size is not able to moderate the relationship between ineffective monitoring and fraud in financial statements. Practical implication: The theoretical implication of this research is to increase academic knowledge about the factors that cause fraudulent financial statements.